THE INFLUENCE OF SHOES IN THE SOIL REACTION FORCE DURING THE PRACTICE OF HYDROGIMNASTIC EXERCISES (Fiep Bulletin - online, 2014)
This study was aimed to verify the soil upright reaction force, during the demonstration of four exercises with and without the wear of shoes. Fifteen female hydrogimnastic teachers that have given classes for, at least, six months participated in the study.  For the assessment, two AMTI force platforms were used. For the data comparison, it was used descriptive statistics, Shapiro-Wilk and t test with meaning of 5%. There was not uniform tendency of modification in the maximum force related to wearing or not wearing tennis shoes. In most part of the analyses, differences when the teacher was demonstrating the movements with and without tennis shoes were not observed.
Keywords: influence of shoes; soil upright reaction force; hydrogimnastics exercises